Implementasi Corporate Social Responsibility Melalui Program Bank Indonesia Mengajar - Hakim, Lukman Fauzan; Novianti, Evi; Kadarisman, Ade; Khoerunnisa, Lutfi (Jurnal Representamen, 2022)
Corporate Social Responsibility (CSR) is a phenomenon and strategies used by the company to accommodate the needs of stakeholder (Santoso, 2016). One of the agencies implementing CSR is KPw Bank Indonesia Jawa Barat. The purpose of this research is to discover the implementation of Corporate Social Responsibility in Bank Indonesia Mengajar Program by KPw Bank Indonesia Jawa Barat. The method used in this research is descriptive study with qualitative approach and paradigm of positivistic. The technique of data collected by through in-depth interview, observation, documentation and literature study. This research showed that in the planning phase of Bank Indonesia Mengajar Program was in line with various aspects such as the program implementation regulation was listed in “Peraturan Dewan Gubernur No.14/14/PDG/2012 concerning about PSBI Program”, the vision and mission of Bank Indonesia. However, KPw Bank Indonesia Jawa Barat was not doing a research as a part of planning phase. In implementation phase of Bank Indonesia Mengajar Program, has been running well. The obstacles in implementing program just only occurred in technical matters. In the checking phase, KPw Bank Indonesia Jawa Barat do the checking with the form of a report and given the report to two parties, namely internal leaders and external stakeholder. Last in the evaluation phase, evaluation carried out after the program was done. The evaluation carried out in two forms, that is formal evaluation do in the form of meeting with leaders and non-formal in the form of discussions with the implementing team. However, in the evaluation phase stakeholder were not involved. Suggestion for KPw Bank Indonesia Jawa Barat, it would be better if they are do the research as a part of planning program and involves the stakeholders in the evaluation phase of Bank Indonesia Mengajar program.